Age-Related Differences in the Neural Processing of Idioms: A Positive Perspective - Yeh, Su-Ling; Li, Shuo-Heng; Jingling, Li; Goh, Joshua O. S.; Chao, Yi-Ping; Tsai, Arthur C. (Frontiers in Aging Neuroscience, 2022)
We examined whether older adults benefit from a larger mental-lexicon size and world knowledge to process idioms, one of few abilities that do not stop developing until later adulthood. Participants viewed four-character sequences presented one at a time that combined to form (1) frequent idioms, (2) infrequent idioms, (3) random sequences, or (4) perceptual controls, and judged whether the four-character sequence was an idiom. Compared to their younger counterparts, older adults had higher accuracy for frequent idioms and equivalent accuracy for infrequent idioms. Compared to random sequences, when processing frequent and infrequent idioms, older adults showed higher activations in brain regions related to sematic representation than younger adults, suggesting that older adults devoted more cognitive resources to processing idioms. Also, higher activations in the articulation-related brain regions indicate that older adults adopted the thinking-aloud strategy in the idiom judgment task. These results suggest re-organized neural computational involvement in older adults’ language representations due to life-long experiences. The current study provides evidence for the alternative view that aging may not necessarily be solely accompanied by decline.